Tapentadol hydrochloride: A novel analgesic - Singh, Dewan Roshan (Medknow Publications & Media Pvt Ltd, 2013)
Tapentadol is a novel, centrally acting analgesic with dual mechanism of action, combining mu-opioid receptor agonism with noradrenaline reuptake inhibition in the same molecule. It has an improved side effect profile when compared to opioids and nonsteroidal anti-inflammatory drugs. The dual mechanism of action makes Tapentadol a useful analgesic to treat acute, chronic, and neuropathic pain.